Sudden Cardiac Arrest in Athletes: Current Perspectives on Prevention and Emergency - A Narrative Review - Kuc, Katarzyna Jolanta; Jakubiak, Patryk; Zegadło, Katarzyna; Dobrucki, Maciej; Brzezicki, Krzysztof; Krakowiak , Dominika; Nieradka, Kornelia (Quality in Sport, 2026)
Background: Sudden cardiac arrest (SCA) in athletes is a leading cause of exercise-related mortality driven by underlying cardiac substrates and exertional triggers. Aim: The primary objective of this narrative review is to summarize and evaluate current evidence regarding the etiology, epidemiology, pathophysiology, and prevention strategies of SCA in athletes, while highlighting essential protocols for on-field emergency management. Material and methods: This review synthesizes data from global registries and clinical studies to analyze SCA incidence, screening models, and survival outcomes. Results: SCA incidence ranges from 1:40,000 to 1:80,000 athlete-years, with higher risks in male (5.55-fold) and Black athletes (nearly 3-fold). Primary causes include hypertrophic cardiomyopathy (36% of US fatalities) and coronary anomalies (12%–14%), triggered by exercise-induced adrenergic surges. The 2017 International Criteria for ECG have reduced false-positives to ~3%. Witnessed SCA with defibrillation within 3 minutes yields an 68%–89% survival rate, vastly outperforming the general population (8%–10%). Conclusions: Preventing SCA mortality requires optimized screening, rehearsed venue Emergency Action Plans, immediate AED access, and genetic cascade screening for inherited conditions.